2010
DOI: 10.1002/term.343
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms of structure generation during plastic compression of nanofibrillar collagen hydrogel scaffolds: towards engineering of collagen

Abstract: Operator control of cell/matrix density of plastically compressed collagen hydrogel scaffolds critically depends on reproducibly limiting the extent of scaffold compaction, as fluid expulsion. A functional model of the compression process is presented, based on the idea that the main fluid-leaving surface (FLS) behaves as an ultrafiltration membrane, allowing fluid (water) out but retaining collagen fibrils to form a cake. We hypothesize that accumulation of collagen at the FLS produces anisotropic structuring… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(22 citation statements)
references
References 58 publications
(88 reference statements)
0
22
0
Order By: Relevance
“…20,21 In this study, cells are in contact with the FLS of the CC constructs and the nFLS of the UC constructs. It is well known that soluble factors, cell-extracellular matrix interactions as well as external mechanical loads influence cell proliferation and differentiation.…”
Section: Discussionmentioning
confidence: 99%
“…20,21 In this study, cells are in contact with the FLS of the CC constructs and the nFLS of the UC constructs. It is well known that soluble factors, cell-extracellular matrix interactions as well as external mechanical loads influence cell proliferation and differentiation.…”
Section: Discussionmentioning
confidence: 99%
“…37 It has also been reported that the formation of a dense collagen region during plastic compression of collagen gels has increased hydraulic resistance of hydrated gels, as well as diminishing the fluid flow through the construct. 38,39 In addition, after transplantation, the bladder could have a tube for drainage during the time of healing. Risk for intraperitoneal leakage is then small.…”
Section: One-stage Tissue Engineering Of Bladder Wall Patchesmentioning
confidence: 99%
“…In addition, other techniques such as plastic compression could also be applied to reduce water content and increase the overall material stiffness. [55][56][57] …”
Section: Ahearne and Lynchmentioning
confidence: 99%